Efficient Electrochemical Nitrogen Fixation over Isolated Pt Sites - Hao, Ran; Sun, Wenming; Liu, Qian; Liu, Xiaolu; Chen, Jialiang; Lv, Xianwei; Li, Wei; Liu, Yu‐ping; Shen, Zhurui (Small (Weinheim an der Bergstrasse, Germany), 2020)
Recently, ambient electrochemical N2 fixation has gained great attention. However, the commercial Pt‐based electrocatalyst hardly shows its potential in this field. Herein, it is found that the isolated Pt sites anchored on WO3 nanoplates exhibit the optimum electrochemical NH3 yield rate (342.4 µg h−1 mg−1Pt) and Faradaic efficiency (31.1%) in 0.1 m K2SO4 at −0.2 V versus RHE, which are about 11 and 15 times higher than their nanoparticle counterparts, respectively. The mechanistic analysis indicates that N2 conversion to NH3 follows an alternating hydrogenation pathway, and positively charged isolated Pt sites with special Pt−3O structure can favorably chemisorb and activate the N2. Furthermore, the hydrogen evolution reaction can be greatly suppressed on isolated Pt sites decorated WO3 nanoplates, which guarantees the efficient going‐on of nitrogen reduction reaction. Isolated Pt atoms anchored on WO3 nanoplates exhibit highly active for ambient ammonia electrosynthesis, which is ascribed to facilitated chemisorption and activation of nitrogen and effective suppression for hydrogen evolution reaction (HER), immensely enhancing NH3 yield rate and Faradic efficiency. This groundbreaking research presents Pt‐based nanocatalysts for electroreduction of nitrogen and provides an idea for the HER depression.